Modeling food web structure and selenium biomagnification in lake macquarie, New South Wales, Australia, using stable carbon and nitrogen isotopes. (6th February 2015) - Schneider, Larissa; Maher, William A.; Potts, Jaimie; Taylor, Anne M.; Batley, Graeme E.; Krikowa, Frank; Chariton, Anthony A.; Gruber, Bernd
Abstract As a consequence of coal‐fired power station operations, elevated selenium concentrations have been reported in the sediments and biota of Lake Macquarie (New South Wales, Australia). In the present study, an ecosystem‐scale model has been applied to determine how selenium in a seagrass food web is processed from sediments and water through diet to predators, using stable isotopes (δ13C and δ15N) to establish the trophic position of organisms. Trophic position, habitat, and feeding zone were examined as possible factors influencing selenium bioaccumulation. Selenium concentrations ranged from 0.2 μg/g dry weight in macroalgae species to 12.9 μg/g in the carnivorous fish Gerres subfasciatus. A mean magnification factor of 1.39 per trophic level showed that selenium is biomagnifying in the seagrass food web. Habitat and feeding zone influenced selenium concentrations in invertebrates, whereas feeding zone was the only significant factor influencing selenium concentrations in fish. The sediment–water partitioning coefficient (Kd) of 4180 showed that partitioning of selenium entering the lake to particulate organic material (POM) is occurring, and consequently availability to food webs from POM is high. Trophic transfer factors (invertebrate = 1.9; fish = 1.2) were similar to those reported for other water bodies, showing that input source is not the main determinant of the magnitude of selenium bioaccumulation in a food web, but rather the initial partitioning of selenium into bioavailable POM. Environ Toxicol Chem 2015;34:608–617. © 2014 SETAC